POST-PANDEMY GLOBAL ORDER CHANGES - Mulyana, Budi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research was to enrich predictive analysis in the study of international relations, especially those related to global issues. The study used qualitative research methods with data collection techniques through literature studies. The result showed that the study of the pandemic situation, provides new conditions in state behavior as well as international interactions. However, in order to arrive at a change in global order, certain preconditions are needed. This research concludes that certain preconditions required in changing the global order have not yet been realized so that the direction of change in the global order has not been seen by itself.